A linear polyethylenimine (LPEI) drug conjugate with reversible charge to overcome multidrug resistance in cancer cells. (12th October 2015) - Zhou, Zhuxian; Murdoch, William J.; Shen, Youqing
Abstract: Multidrug resistance (MDR) is an important hindrance to efficient cancer chemotherapy. Cancer cell lysosomes play an important role in intrinsic MDR by accumulating chemotherapy drugs and deactivating their therapeutic action. The cationic polymer polyethyleneimine (PEI) can disrupt the endosomal/lysosomal membrane via the proton-sponge effect (PSE). However, its positive charge makes it toxic and so it cannot be used in vivo . Here, linear PEI (LPEI) is used to demonstrate that a pH-triggered charge-reversal carrier can solve this problem. The imines are amidized by masking a lysosomal pH-active agent. LPEI regenerates its positive charge in the acidic endosomal/lysosomal cell compartments and disrupts the endosomal/lysosomal membrane, resulting in delivery of the drugs into the cytoplasm and nuclei where they exert their pharmacologic activity. Folic acid targeting groups are introduced into the polymer to increase its cancer-cell targeting capability. An anticancer drug camptothecin (CPT) conjugated to the carrier by intracellular cleavable disulfide bonds shows improved cytotoxicity over free CPT. Graphical abstract: Targeted charge-reversal LPEI conjugate structure and its acid-triggered charge reversal (A) and nuclear drug delivery (B): The negatively charged drug conjugate accumulates in cancer tissues via the enhanced permeation and retention effect; it is taken up by the cancer cells via folate receptor-mediated endocytosis, transferred into an endosome and then a lysosome; the labile amides hydrolyze at the acidic tumor microenvironment (pH < 7.0), endosome (pH = 6.0–6.5) and lysosome (pH = 4.5–5.5) to regenerate the LPEI as the carrier. The regenerated LPEI carrier ruptures the lysosomal membrane to escape into the cytosol and traverse into the nucleus and releases the carried drug there. Highlights: We have demonstrated cancer cell nucleus-targeted drug delivery by a LPEI drug conjugate. LPEI drug conjugate has a different charge-reversal profile with the PLL drug conjugate. LPEI drug conjugate can overcome the intracellular drug resistance and deliver drug to the cell nucleus. LPEI-based drug conjugate showed improved cytotoxicity over free drug.